Network based E-learning system for secondary school - Choong Hooi, Goh (2011)
Most of the secondary school in Malaysia is still using traditional data storing in terms of hardcopy (Paper) then store those record in a special record keeping store room. Sometime this traditional data storing can cause a lots of problems, e.g.damage,data/record lost,and longer time to retrieve when we want to get an older record.Traditional teaching method in secondary school also causes some problems to student.Students have to bring a lot of textbooks to school every day and sometime the weight goes up to 10Kg to carry every day.With the growing of Information and Communication Technology (ICT) in Malaysia, this situation should be changed.The Elearning system can provide the solution for the above situation. There are four targeted user groups in this system which is admin,teacher,student and parent.For admin/staff, users are able to manage student's record.They are able to create a new student profile,update infoimation and create login account for student and teacher also.For student, students are able to view their profile,request update on their profile and view their result mark or study performance.They are also able to download extra notes, quiz,home work,class activity etc from the system uploaded by their teachers.For teacher,teachers are able to upload and view their student result and give comment according to their performance.Besides that,they are also able to upload extra notes,questions,activities etc to the system according t6 their own subject.For parent,parents are able to view their child result performance and able to ask the teacher about their child situation in school. .